Hvor universelt er det universelle i kristendommen?: En præsentation of kritik af Svend Andersens disputats - Gregersen, Niels Henrik (Religionsvidenskabeligt tidsskrift, 1991)
The highlight of the dissertation, Sprog og Skabelse, is the reevaluation of the neglected phenomenologist Hans Lipps (1889-1941), who is seen by Andersen to be the phenomenological counterpart to the philosophy of the later Wittgenstein, and even in several aspects as superior to it. In a valuable account of Løgstrup's philosophy of language, Andersen furthermore interprets the philosophy of religion by K.E. Løgstrup (1905-1981) as constituting a continuation of Lipps' philosophy of language.The article questions some lines of this interpretation. The theological motives of Løgstrup's early thinking are not derived from Lipps, but rather from Bultmann's and Gogarten's existentialist theology, combined with Løgstrup's own ideas on the givenness of life-utterance. In his philosophy of religion, Løgstrup persistently underlines the resistance that our language receives from the created structures of reality. His metaphysics determines his views on language, not the other way round. Another point of critique concerns Andersen's attempt to revive a natural theology based on the term of God as "the power to be in everything that exists". The article objects that this concept is semantically ambiguous until it is defined in the metaphorical framework of one or another religious tradition. The problem of analytical philosophy is its tendency to neglect the embeddedness of religious concepts in the history of the language. There are no such things as immaculate concepts.